Entre Nubes Y Recuerdos: Proyecto documental para preservar la memoria histórica del Cerro del Cable (2023)
The Entre Nubes y Recuerdos project seeks to preserve the historical memory of the Cerro del Cable community in Bogotá, Colombia, through a series of audiovisual narratives. This is because a generational disconnect was evident in the community, caused by the loss of oral tradition, which is attributed to multiple factors such as urbanization, technology, and changes in lifestyles. To achieve this goal, a participatory ethnographic methodology focused on graphic design was implemented, which seeks to understand the social and cultural practices of a group of people in order to identify the needs of the users. This is done through observation, interviews, and active participation.